Balancing Local Community Interest and International Responsibilities in the Context of the Expulsion of Rohingya Refugees in Aceh - Havez, Muhammad; Ernawati, Ninin; Pitaloka, Diva; Rosidi, Ahmad; Jumadi, Joko (UI Scholars Hub, 2024)
At the end of 2023, a group of refugees that came to the Aceh region committed several acts of misconduct that shocked Indonesia. Such acts included throwing away rice that was given to them by the Acehnese residents, who did so as an act of kindness. However, the refugees disappointed the Acehnese residents with their response. Due to this, the Acehnese residents insist on expelling the refugees from their area, but the local government needed clarification in order to determine their position. On one hand, it is important to take note of the concerns of the Indonesian people, however, there is also a need to protect international refugees. Based on this understanding, this article will discuss what actions the Indonesian government can take in response to the phenomenon between the Acehnese residents and Rohingya refugees. Moreover, what solutions can the Indonesian government provide in order to balance the interests of local communities and international responsibilities, in the context of the expulsion of Rohingya refugees in Aceh? This article concludes that policymakers and stakeholders must collaborate to develop comprehensive solutions that address the needs of the local community and the refugees, fostering a more sustainable and empathetic response to refugee challenges in the future. This study emphasizes the importance of forging a synergy between local and global perspectives in order to acknowledge the interdependence of community interests and international responsibilities in pursuing effective refugee management.